Effects of ketamine on fear memory extinction: a review of preclinical literature - Boese, Martin; Berman, Rina; Radford, Kennett; Johnson, Luke R.; Choi, Kwang (Frontiers in Neuroscience, 2025)
IntroductionKetamine, a multimodal dissociative anesthetic, is widely used as a trauma analgesic in emergency situations. Ketamine is also used to treat psychiatric disorders due to its broad application potential, including treatment-resistant major depression. However, its impacts on the development of post-traumatic stress disorder (PTSD) and its potential as a treatment for PTSD are controversial. PTSD is marked by persistent and intrusive memories of traumatic event(s) and re-experiencing of the traumatic memories when exposed to trauma-related stimuli. Individuals with PTSD are often treated with prolonged exposure therapy (PE), in which they are gradually exposed to stimuli that remind them of the previous traumatic memory. If successful, they may learn that the previously traumatic stimuli are no longer threatening, a process known as fear extinction. Although fear extinction can be studied in laboratory animals, previous preclinical literature on the effects of ketamine on fear extinction has been inconsistent.MethodsThus, we summarized the existing preclinical literature examining effects of ketamine on fear extinction and its potential molecular mechanisms.ResultsStudies found that ketamine may enhance, impair, have no effect, or have mixed effects on fear extinction. These discrepancies may be attributed to differences in dosage, route, and timing of ketamine administration.DiscussionWe conclude the review with recommendations for future research on ketamine and PTSD such as the inclusion of more female subjects, clinically relevant doses and routes of ketamine administration, and more comprehensive behavioral assays that are relevant to PTSD in humans to enhance translation between preclinical and clinical research.